دراسة مستويات المغنيزيوم في المصل عند مرضى الربو القصبي البالغين - حجازية مالك; دويبة راما (Latakia University Journal -Medical Sciences Series, 2019)
Background: Asthma represents one of the most common chronic diseases and is a major puplic health proplem worldwide. Serum magnesium has several effects on smooth muscles in the bronchial walls, which may be related to protection from poor control in patients and the severity of symptoms and frequency and severity of attacks. Aim:Assessment the level of serum magnesium in patients with bronchial asthma. Materrials and Methods:This was a case-control study conducted at Tishreen University Hospital,Lattakia,Syria, during the period between February2018, February2019 .This study included 112 subjects divided into two groups,First group included 56 adults asthmatic patients (20male,36female), their ages ranged from 18 to 50 years with a mean age of (36.3±7.9),this group divided into two parts, first one 28 chronic stable asthma patients and the second one 28 patients with acute exacerbation.The second group included 56 healthy adult (23male, 33female) as a control group,their ages ranged from 18 to 50 years with a mean age of (34.8±8.2).All subjects in this study were submitted to full medical history and clinical examination,calculation of body mass index (BMI),spirometry and detection of serum magnesium level by colorimetric method.SPSS software was used for data analysis. P-value<0.05 was considered as statistically significant. Results:The study showed that serum magnesium level was significantly decreased in asthmatic patients (1.5±0.2mg/dl) as compared with the healthy control group(2.1±0.1mg/dl). And serum magnesium level was significantly decreased in patients with acute exacerbation as compared with the chronic stable patients. Magnesium levels had a significant positive correlation with FEV1% predicted, and FEV1/FVC . Conclusion: There is an important relationship between bronchial asthma in adult and serum magnesium levels. خلفية: يمثّل الربو واحداً من أشيع الأمراض المزمنة و هو مشكلة صحيّة عامّة على المستوى العالمي. يملك مغنيزيوم المصل تأثيرات عديدة على العضلات الملساء في جدر القصبات , والتي قد تكون ذات صلة بالحماية من اضطراب الضبط عند المرضى وشدة الأعراض وتكرار وشدة الهجمات. الهدف : تقييم المستوى المصلي للمغنيزيوم عند مرضى الربو القصبي . المواد والطرق: كانت هذه دراسة حالة- شاهد أجريت في مستشفى تشرين الجامعي في اللاذقيّة/سوريا , خلال الفترة الممتدة ما بين شباط 2018 – شباط 2019, على 112 شخص تم تقسيمهم إلى مجموعتين: المجموعة الأولى شملت 56 مريض ربو بالغ (20ذكر,36 أنثى) تراوحت اعمارهم ما بين 18-50 سنة مع متوسط عمر 36.3±7.9 موزعين ضمن مجموعتين: الأولى مجموعة الربو المستقر المزمن(28)مريض,الثانية مجموعة مرضى الهجمة الربويّة الحادة(28) مريض. المجموعة الثانية شملت 56 شخص طبيعي (23ذكر,33أنثى) كمجموعة شاهد , تراوحت أعمارهم ما بين 18-50 سنة مع متوسط عمر 34.8±8.2 . خضع جميع الأفراد المشاركين في هذا البحث لاستجواب دقيق , فحص سريري, حساب مشعر كتلة الجسم (BMI) , اختبار وظائف الرئة (Spirometry) , وقياس المستوى المصلي للمغنيزيوم بالطريقة اللونيّة. تم استخدام البرنامج الاحصائي (SPSS) لتحليل البيانات. تم اعتبار القيمة التنبؤيّة (P-value) أقل من 0.05 هامة احصائيّا˝. النتائج: أظهرت الدراسة أنّ مستوى مغنيزيوم المصل لدى المرضى الربويين (1.5±0.2 مغ/دل) كان أخفض بفارق هام احصائيّا˝ بالمقارنة مع مجموعة الشاهد (2.1±0.1 مغ/دل) . وأنّ مستوى مغنيزيوم المصل لدى مرضى الهجمة الربويّة الحادة كان أخفض بفارق هام احصائيّا˝ بالمقارنة مع مرضى الربو المستقر المزمن. كان هنالك علاقة ايجابيّة هامة حصائيّا˝ بين مستوى مغنيزيوم المصل و نسبة FEV1 من القيمة المتوقعة , ونسبة FEV1/FVC. الخلاصة: هناك علاقة هامة بين الربو القصبي عند البالغين ومستويات مغنيزيوم المصل.